Vaporwave, Nostalgic Reaestheticization and the Cultural Mechanisms of Digital Capitalism - Aleksandr Shutenkov (új szem, 2025)
The contemporary paradigm of digital hauntology is obsessed with the experience of non-digital humans interacting with digital reality. Humans interact with the ghostly traces of machines, endlessly re-aestheticizing and remixing their own experience of using interfaces, and their experience of interacting with digital media. Machines are constantly improving, their ability to generate content is increasing, but humans are still a purely biological species, they are frozen on the threshold of transgression. With each cycle of machine upgrades, with each leap in performance in generating media content, humans are left with more and more ghostly traces. Hauntology becomes a totality for modern man, he operates only with ghosts in his culture. The ghosts of the capitalist past, and of the capitalist future, these ghosts cannot be mourned, because to mourn such ghosts, we must first know their essence, know the accelerating machine of digital capitalism that consciously and unconsciously produces nostalgic spaces, structures, and entities. Everything we interact with today is an artificially constructed system saturated with the aesthetic echoes of a virtual capitalist paradise. Vaporwave attempts to fill in the gaps in human understanding of the machine; it reproduces the alienating, shrouding experience of human understanding of machine reality. The vaporwave is an ontological paradigm for human existence in the face of the impossibility of fully understanding an ever-accelerating irreality. It is a reductionist and reactionary paradigm of being that maintains the status quo of significant agents of digital capitalism and proposes blissful oblivion in constructed irreality as opposed to immediate and permanent human-machine transgression.